Assessing the Role of Zakat and Murabahah Financing in Improving Islamic Bank Performance - Dama Mustika; Anis Mahmudah Dariati (Etihad: Journal of Islamic Banking and Finance, 2026)
Introduction: Financial performance is a key indicator of the sustainability and competitiveness of Islamic Commercial Banks in Indonesia. Previous studies have reported inconsistent findings on the effects of zakat and murabahah financing on bank profitability, while limited research has simultaneously examined their impacts on Return on Assets (ROA) and Return on Equity (ROE) using legitimacy theory. This study investigates their influence on Islamic bank performance. Research Methods: A quantitative approach was employed using panel data regression analysis on eight Islamic Commercial Banks selected through purposive sampling during 2019–2023. Results: Zakat (β = 0.000214; p = 0.0421) and murabahah financing (β = 0.000543; p = 0.0158) positively and significantly affect ROA but have no significant effect on ROE. The ROA model explains 45.20% of the variation in profitability, whereas the ROE model explains only 6.50%. Conclusion: Zakat and murabahah financing improve asset utilization efficiency and strengthen organizational legitimacy, although their contribution to shareholder return efficiency remains limited.